THEOLOGIES OF FEMININE MEDIATION: HINDU AND CHRISTIAN - Martin, Judith G (Journal of Dharma, 1981)
When compared with the complexity of the goddess tradition in Hinduism, the Christian treatment of the sacred feminine, as this is epitomized in the portrayals of Sophia and the Virgin Mary, is noticeably restrained and unambiguous. Whereas the images of the latter almost always l reflect that aspect of the Ultimate which is playful, creative, nourishing, life-giving, compassionate, pure and wise, the §akti or female principle of power in Hinduism embodied, in addition to the qualities just mentioned, other more aggressive and destructive tendencies. For example, Usas, the beautiful and youthful Vedic goddess of the dawn was described as being rebellious, destructive, a warrior 2 ; and Käli, the goddess of war, has been pictured from time immemorial as being blood-thirsty, who slays the enemy and sucks his blood. The contrast between the Hindu and Christian traditions can be expressed in symbolic language. The former traditionally has associated the goddess with both the breast and the tooth; the latter has focussed on the breast to almost the total exclusion of the more violent or fierce aspects.